2019
DOI: 10.3390/ijerph17010161
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exergame Training and Detraining on Lower-Body Strength, Agility, and Cardiorespiratory Fitness in Women with Fibromyalgia: Single-Blinded Randomized Controlled Trial

Abstract: The aim of this study was to analyze the effects of a 24 week exergame intervention and 24 weeks of detraining on lower-limb strength, agility, and cardiorespiratory fitness in women with fibromyalgia (FM). It was performed as a single-blinded randomized controlled trial of 55 women with FM. University facilities were used. The 24 week exergame intervention was focused on mobility, postural control, upper- and lower-limb coordination, aerobic fitness, and strength. Participants performed 120 min of exergaming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(52 citation statements)
references
References 45 publications
3
49
0
Order By: Relevance
“…Different articles focused on the primary outcomes (i.e., electroencephalography, physical fitness, and quality of life) of the trial have been recently published [32,[36][37][38]. Nevertheless, the hypothesis in the present study is entirely novel (improvements in different volumetric brain structures after an exergame intervention) and significantly differs from the other articles.…”
Section: Trial Designmentioning
confidence: 78%
See 1 more Smart Citation
“…Different articles focused on the primary outcomes (i.e., electroencephalography, physical fitness, and quality of life) of the trial have been recently published [32,[36][37][38]. Nevertheless, the hypothesis in the present study is entirely novel (improvements in different volumetric brain structures after an exergame intervention) and significantly differs from the other articles.…”
Section: Trial Designmentioning
confidence: 78%
“…Furthermore, this hypothesis may be reinforced by the results of Nieman et al [66], where they did not find volumetric changes after six months of intervention but did after 12 months. However, the 24-week exergame-based intervention has previously shown significant effects in physical fitness [36,38], quality of life and pain [36], autonomic modulation [37], and even in the EEG beta power spectrum [32] in women with FM. Interestingly, this could indicate that brain volume-related changes need more time to be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 We found that improvement in physical performance was significantly higher in the VRG than in the CTG. In the literature, there are studies reporting improvement in cardiovascular fitness, 21,30 adaptation, 25 and mobility. 24 It is POLAT ET AL.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21][22][23][24] Motion-controlled videogames targeting virtual reality are examples of these exercises. When we searched the studies about virtual reality exercises that are used in rehabilitation of patients with fibromyalgia, it has been shown that virtual reality exercises reduce fear of falling and static balance problems, 21 improve autonomic balance, 25 reduce pain, [26][27][28][29] increase healthy-related quality of life [27][28][29] and exercise capacity, 26,29 promote cardiovascular fitness, 26,30 and decrease the impact of FMS and fatigue. 26 It was also stated that these exercises motivated patients, increased patient compliance and patient satisfaction, and promoted psychological process (general mood state, positive emotions, motivation, and self-efficacy) in the rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…In the two cited studies [ 23 , 26 ], which assess the muscular strength of the lower limb after TKA surgery, in both cases no major impact of VR rehabilitation was demonstrated. Other authors’ reports noted the benefit of using VR to increase muscular strength in women with risk of falling [ 68 ], whereas Villafaina et al [ 69 ] noted that the increase in muscular strength through exergames training obtained in women with fibromyalgia is greater but short-lived.…”
Section: Discussionmentioning
confidence: 99%